Effect on Mental Health of a Participatory Intervention to Improve Psychosocial Work Environment: A Cluster Randomized Controlled Trial among Nurses. Issue 3 (4th October 2013) - Uchiyama, Ayako; Odagiri, Yuko; Ohya, Yumiko; Takamiya, Tomoko; Inoue, Shigeru; Shimomitsu, Teruichi
Abstract : Effect on Mental Health of a Participatory Intervention to Improve Psychosocial Work Environment: A Cluster Randomized Controlled Trial among Nurses: Ayako UCHIYAMA, et al . Department of Preventive Medicine and Public Health, Tokyo Medical University, Japan— Objectives: Improvement of psychosocial work environment has proved to be valuable for workers' mental health. However, limited evidence is available for the effectiveness of participatory interventions. The purpose of this study was to investigate the effect on mental health among nurses of a participatory intervention to improve the psychosocial work environment. Methods: A cluster randomized controlled trial was conducted in hospital settings. A total of 434 nurses in 24 units were randomly allocated to 11 intervention units (n=183) and 13 control units (n=218). A participatory program was provided to the intervention units for 6 months. Depressive symptoms as mental health status and psychosocial work environment, assessed by the Job Content Questionnaire, the Effort‐Reward Imbalance Questionnaire, and the Quality Work Competence questionnaire, were measured before and immediately after the 6‐month intervention by a self administered questionnaire. Results: No significant intervention effect was observed for mental health status. However, significant intervention effects were observed in psychosocial work environment aspects, such as Coworker Support ( p <0.01) and Goals ( p <0.01), and borderline significance was observed for Job Control ( p <0.10). Conclusions: It is suggested that a 6‐month participatory intervention is effective in improving psychosocial work environment, but not mental health, among Japanese nurses.